BIOETIKA ISLAM KLONING TRANSPLANTASI ORGAN DAN BATASAN SYARIAH - Imam Baidhawi (Yayasan An-Nur Meunara Baro, 2025)
The advancement of modern biotechnology, particularly in the fields of cloning and organ transplantation, has raised significant ethical and legal challenges from an Islamic perspective. This study aims to analyze the boundaries of Sharia regarding cloning and organ transplantation practices, guided by the principles of maqāṣid al-sharī'ah. A qualitative research method was employed, involving analysis of primary and secondary literature, including fatwas from Islamic institutions such as the Indonesian Ulema Council (MUI) and Majma' al-Fiqh al-Islami, as well as Scopus-indexed scholarly articles published. The findings reveal that human reproductive cloning is strictly prohibited as it violates the essence of divine creation and threatens social structures, while therapeutic cloning is conditionally permitted for medical purposes. Organ transplantation is permissible under strict conditions, including donor consent, prohibition of commercialization, and ensuring greater benefits over harms. The study emphasizes the necessity of Sharia-based regulations and a collective ijtihad approach to ensure biotechnological advancements align with Islamic values. It recommends enhancing Islamic bioethics literacy and fostering collaboration among stakeholders to develop an ethical framework that balances medical innovation with the preservation of human dignity.